Epidemiology, comorbidities, and healthcare utilization of patients with chronic urticaria in Germany - Weller, K.; Maurer, M.; Bauer, A.; Wedi, B.; Wagner, Nicola; Schliemann, S.; Kramps, T.; Baeumer, D.; Multmeier, J.; Hillmann, E.; Staubach, P. (Journal of the European Academy of Dermatology and Venereology, 2021)
Background: Comprehensive data on the epidemiology and comorbidities of chronic urticaria (CU) in Germany are either limited, or not contemporary. Objectives: To investigate the epidemiology of CU, overall comorbidities and healthcare resource utilized by patients with CU in Germany, using an anonymized statutory health insurance (SHI) database. Methods: Anonymized SHI claims research database of the Institute for Applied Health Research, Berlin [InGef] (01 January 2015–30 September 2018) was used to analyse insured individuals with a confirmed diagnosis of CU (ICD-10-GM codes). Twelve-month diagnosed prevalence and incidence, comorbidities (vs. atopic dermatitis and psoriasis), and healthcare utilization by patients with CU were investigated. Results: Of 4 693 772 individuals of all ages listed in the database, 3 538 540 were observable during 2017. Overall, 17 524 patients (˜0.5%) were diagnosed with CU; chronic spontaneous urticaria (CSU: 71.2%), chronic inducible urticaria (CIndU: 19.7%), CSU+CIndU (9.1%). Females, vs. males, had higher diagnosed prevalence (0.62% vs. 0.37%) and diagnosed incidence (0.18% vs. 0.11%) of CU among all patients. Patients most frequently visited general practitioners (41.3% of total visits). Hypertensive diseases (43.5%), lipoprotein metabolism disorders (32.1%) and affective disorders (26.0%) were the most frequently reported comorbidities of special interest. Rates of most comorbidities of special interests were similar to atopic dermatitis and psoriasis patients, and all higher vs. overall population. More than half (54.1%) of all CU patients were not prescribed any treatment. Second-generation H1-antihistamines were the most commonly prescribed medication for adult (17.9%) and paediatric (27.9%) patients. Patients with CIndU (paediatric, 15.5%; adult, 7.8%) were more often hospitalized versus patients with CSU (paediatric, 9.9%; adult, 4.6%). Conclusions: In Germany, prevalence of CU along with multiple comorbidities may pose increased burden on the healthcare system. Awareness of adhering to treatment guidelines, and aiming for complete control of urticaria, needs to be driven and may improve outcomes.
CRIS-Team Scopus Importer:2021-11-19